Warong Aiskrim D’NANZ: case study: company analysis / Mohd Ishraffil Ezzrail Mohd Jusni … [et al.] - Mohd Jusni, Mohd Ishraffil Ezzrail; Shazman, Rose Aidatul Azita; Muhamad Jamri, Ezzat Imani; Ahmad Khiril Azam, Muhammad Aiman Akmal; Zulkarnain, Nur Kiasatina Anantasha (2021)
Warong Aiskrim D’NANZ is a family business operated by two married couples, Mrs. Azliza and her husband, Mr. Adnan and help by their 3 children as a worker. Their first outlet was launched in November 2020 in Klebang Beach area. They started this business since 2014 by provide a service such as kiosk, order from home and for private events such as wedding and birthday party. After brainstormed the idea of the product that they want to sell, they decided on producing ice cream business and took a course of making ice cream to build their own business empire. For D’NANZ Ice cream’s business strategy, they sell their ice cream at the cheapest price so that everyone can afford to buy their product. Starting with using flavours that bought at a bakery, they started to improve their recipes by using the real fruit itself such as “kelapa pandan” and “durian” because they figured out that using the real fruit makes the ice cream taste better. They came out with this idea so that their customers could eat the ice cream as well as the coconut while they scoop the ice cream inside the coconut. As for case study, we conduct an interview with the founder of Warong Aiskrim D’NANZ to collect information that related with syllabus of Principles of Entrepreneurship. There are nine (9) elements of Business Model Canvas that we used to identify how exactly this family business works and how they manage the marketing and operations strategy to survive in the business market despite the condition of economics and other issues faced by Warong Aiskrim D’NANZ. The major problem facing by Warong Aiskrim D’NANZ is a sharp decline in sales revenue for 2 years since Movement Control Order was announced on March 2020. In addition of the major problems facing by this business is lack of marketing. Main causes of this major problems are lack of skills in managing social media and market segmentation. This business is open to all types of consumers as they sell variety of homemade ice-cream yet it is less well known in the market. There are some advantages and disadvantages for each solution that we provide for Warong Aiskrim D’NANZ such as building a sales and marketing team within the company is that the company can determine the most successful approaches with a more well-defined strategy and building more engagements with social media audiences is the risk of negative publicity.